Patterns of the formation of the structure and properties of the X70 low-carbon steel after high-temperature helical rolling; AIP Conference Proceedings; Vol. 2310, iss. 1 : Physical Mesomechanics. Materials with Multilevel Hierarchical Structure and Intelligent Manufacturing Technology - Gordienko A. I. Antonina Ildarovna (2020, 2020)
Title screen